Examination of Turkish Football Fans' Brand Evangelism (Efangelism) Levels and Intention to Purchase - Yüzgenç, Ayşe Asli; Doğan, Hakan; Koç, Mustafa Can (Lahore Medical and Dental College, 2022)
Background: Sport consumers display a different set of values, attitudes and behaviors. Not all football consumers are equally passionate and fanatical. The purpose of this research is to examine the evangelistic attitudes of Turkish football fans towards the team brand and their intention to purchase the licensed sports products of the club. Method: The study group of the research consists of 633 volunteers who are supporters of Fenerbahçe, Galatasaray and Beşiktaş and live in various parts of Turkey. We used the Sports Team Evangelism (eFangelism) Scale-STES as a data collection tool in the research. STES was developed by Dwyer, Greenhalgh, and LeCrom (2015). Its Turkish validation and reliability tests were done by Yüksekbilgili (2017). We also used the "Purchase Intention Scale" developed by Kazançoğlu and Baybars (2015) based on the research of Kwon et al., (2007). Descriptive statistics, Mann Whitney U test and Kruskal Wallis test were used in the analysis of the data. The sources of significant differences in the Kruskal-Wallis test results were distinguished using the Mann-Whitney U Test. Results: The level of evangelism and intention to purchase varied according to the gender of individuals, the team they support, and the amount of spending on licensed products. Conclusion: Our research shows that individuals with a high level of brand evangelism and intention to purchase buy the licensed products of their favorite team more than individuals with a low level of brand evangelism and intention to purchase. In addition, the level of efangelism and intention to purchase of male participants are higher than women. The level of efangelism and intention to purchase of Beşiktaş fans are higher than Galatasaray and Fenerbahçe fans. Keywords: Efangelism, intention to purchase, football fan